Benefits of biobased fertilizers as substitutes for synthetic nitrogen fertilizers: Field assessment combining minirhizotron and UAV-based spectrum sensing technologies - Luo, Hongzhen; Dewitte, Kevin; Landschoot, Sofie; Sigurnjak, Ivona; Robles-Aguilar, Ana A.; Michels, Evi; De Neve, Stefaan; Haesaert, Geert; Meers, Erik (Frontiers in Environmental Science, 2022)
Recovery of biobased fertilizers derived from manure to replace synthetic fertilizers is considered a key strategy to close the nutrients loop for a more sustainable agricultural system. This study evaluated the nitrogen (N) fertilizer value of five biobased fertilizers (i.e. raw pig manure (PM), digestate (DIG), the liquid fraction of digestate (LFD), evaporator concentrate (EVA) and ammonia water (AW)) recovered from an integrated anaerobic digestion–centrifugation–evaporation process. The shoot and root growth of maize (Zea mays L.) under biobased fertilization was compared with the application of synthetic mineral N fertilizer, i.e. calcium ammonium nitrate (CAN). The non-invasive technologies, i.e. minirhizotron and unmanned aerial vehicle (UAV) based spectrum sensing, were integrated with the classic plant and soil sampling to enhance the in-season monitoring of the crop and soil status. Results showed no significant difference in the canopy status, biomass yield or crop N uptake under biobased fertilization as compared to CAN, except a lower crop N uptake in DIG treatment. The total root length detected by minirhizotron revealed a higher early-stage N availability at the rooting zone under biobased fertilization as compared to CAN, probably due to the liquid form of N supplied by biobased fertilizers showing higher mobility in soil under dry conditions than the solid form of CAN. Given a high soil N supply (averagely 70–232 kg ha-1) in the latter growing season of this study, the higher N availability in the early growing season seemed to promote a luxury N uptake in maize plants, resulting in significantly (p < 0.05) higher N concentrations in the harvested biomass of PM, LFD and AW than that in the no-N fertilized control. Therefore, the biobased fertilizers, i.e. PM, LFD, EVA and AW have a high potential as substitutes for synthetic mineral N fertilizers, with additional value in providing easier accessible N for crops during dry seasons, especially under global warming which is supposed to cause more frequent drought all over the world.